ENDIDIKAN KRITIS DAN REFORMASI PENDIDIKAN NASIONAL - Kartono Kartono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2010)
This article efforts to propose a national education reformation by critical education. The critical education is viewed as the most rational medium to reform national education pattern. The critical education is also viewed as capable for empowering students and transforming them in fairly social, cultural, economic and political contexts, be equal and significantly. An education pattern in face democratically and took sides toward difabel society. Key words: national education reformation, critical education.